STUDI KEBUTUHAN DAN UJI COBA AWAL MEDIA FLASHCARD TEMATIK AL-QUR’AN DI PESANTREN ASR, KABUPATEN GOWA - Syinta M; Andi Nurjaya Abadi; Andi Ika Prasasti Abrar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the needs for instructional media and educational technology at Pondok Pesantren Ahlus Shidqi war Rahmah (ASR), Gowa Regency, and to design and conduct an initial trial of a thematic Qur’an learning media using a semi-digital flashcard-based board game. A descriptive qualitative approach was employed, with data collected through interviews, classroom observations, and document analysis. The research results indicate that although facilities such as computers and LCD projectors are available, their use in teaching is still limited due to the lack of diverse and interactive media. Teachers express a need for more engaging and student-centered instructional tools, while students show good adaptability to technology-based learning. The initial testing of the semi-digital board game revealed a positive impact on students' learning motivation, concentration, and confidence in understanding thematic Qur’anic material. These findings suggest that the integration of interactive and contextual media can be an effective strategy to support meaningful and joyful learning experiences in Islamic boarding schools. The research also provides insights into how semi-digital tools can bridge the gap between traditional religious education and modern pedagogical approaches in pesantren environments.